A Case Study on Critical Success Factors of AirAsia - Yerkezhan Mamrina; Daisy Mui Hung Kee; Aidos Tursynbay; Dravyaayajnaah A/P Jayagopal; Hanis Aribah Binti Mohd Athiyah; Rouslan Muhamach (International Journal of Tourism and Hospitality in Asia Pasific, 2020)
Existing literature has frequently highlighted how important are critical success factors in an organization. In this paper, we consider how these critical success factors affect an organization. Organizational success becomes important for many companies because it is very difficult to reach it in this competitive world. This pushed the organizations to improve their structure, strategy and management, and AirAsia is not an exception. AirAsia is one of the biggest low-cost airlines in Asia. It was registered in 1993 but began its activities only in 1996. The Airline company was chosen as the best low-cost airline in the world according to Skytrax eleven times. However, there is still a need for changes and improvements for AirAsia to become better. The findings of this paper have important implications for the managers and practitioners. The implication and recommendations are presented.